Pengaruh Aplikasi Pupuk Hayati Terhadap Dinamika Kelimpahan Mikrob pada Lahan Bekas Tambang Timah yang Ditanami Tanaman Lada (Piper nigrum L.): Biofertilizer Application Influence in Dinamics of Microorganisms Abundance on Tin Mined Area planted Pepper Plant (Piper nigrum L.) - Patimah Siti; Inonu Ismed; Asriani Euis (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
Biofertilizer is a fertilizer containing nine microbial consortia that useful for plant growth. The benefits of using biofertilizers are to improve fertilizer efficiency, maintain fertility soil and plant health, improving yield and sustainability. The aim of this research was to know the effect of the biofertilizer dosage to the population dynamics of microbial abundance of tin mined area planted with pepper plant (Piper nigrum L.). The method used is a direct observation method in the field through soil sampling with a purposive sampling technique. Six Soil samples were taken from every level of treatment. Soil samples were isolated, PDA media for fungi, NA media for bacteria and pikovskaya media for microbes solubilazition phosphate testing for both bacteria and fungi consisting of 54 plates. Result of the research indicate that different dosage of biofertilizers did not affect the dynamics of micro-organisms abundance. Treatment of B4 (10 g L-1 plant-1) gave a good effect on the abundance of fungi. While the treatment of B3 (5 g L-1 plant-1) gave a good effect on bacterial abundance. The result of nitrogen-fixing test was obtained by N inhibiting bacteria on NFB media in the presence of a pellicle at the bottom of the test tube. The result of the phosphate solubilization test was obtained with clear zones surrounded bacteria and fungi. Analyzed six soil samples contained nitrogen-fixing bacteria and Bacillus cereus with bacteria as phosphate solubilization bacteria.